Progress, problems and prospects for standardization of greenhouse-related technologies - Ren, Yanzhao; Wang, Minjuan; Saeeda, Iftikhar Ahmed; Chen, Xuerui; Gao, Wanlin (International Journal of Agricultural and Biological Engineering, 2018)
In recent years, the scale of greenhouse grows rapidly and steadily in China, which promotes the development of greenhouse technology and the demand for standardized technology. However, the standardization process of greenhouse industry in China has been facing with the problem of unbalanced development with the practical standard system for many years. To solve these problems, the most characteristic greenhouse designs used in China contributing to this work are presented in detail. And the development of standard system and the standardization efforts of them are summarized and analyzed in relationship to the data presented in this paper. In this way the origin of greenhouse standard system in China and context of the system development and standardization of greenhouse structure are clarified. It was also found that the development and iterative update of greenhouse standard system are under the influences of enterprises which as the participation of standard constitutors were proved to play an important role in promoting the standardization development of greenhouse. The outcome of this work may be utilized to perfect the greenhouse standardization system and improve the greenhouse standardization efficiency that dominate the facility agriculture in China.Keywords: greenhouse, standardization, standard system, informationization, greenhouse technologyDOI: 10.25165/j.ijabe.20181101.3857Citation: Ren Y Z, Wang M J, Saeeda I A, Chen X R, Gao W L. Progress, problems and prospects for standardization of greenhouse-related technologies. Int J Agric & Biol Eng, 2018; 11(1): 40–48.